2019
DOI: 10.1017/s0007485319000300
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral response and adaptive cost in resistant and susceptiblePlutella xylostellato Chlorantraniliprole

Abstract: Diamides have been used worldwide to manage the diamondback moth (DBM), Plutella xylostella L. (Lepidoptera: Plutellidae), however some strains showed resistance to these molecules. Also, pheromone traps could be used to manage this pest, hence reducing the use of insecticides in the field. Resistant DBM strains may have biological disadvantages in comparison to susceptible strains in areas without sprays, including reduction in fitness or behavioral changes. Therefore, the aim of this study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
0
5
0
3
Order By: Relevance
“…Abbas et al [ 25 ] also found that profenofos-resistant strains of Spodoptera litura have reduced fertility and hatching rates and lower intrinsic growth rates. The resistant strain has shown an adaptive cost in comparison to the susceptible strain, which could result in a delay in population growth in the field [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abbas et al [ 25 ] also found that profenofos-resistant strains of Spodoptera litura have reduced fertility and hatching rates and lower intrinsic growth rates. The resistant strain has shown an adaptive cost in comparison to the susceptible strain, which could result in a delay in population growth in the field [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, a new class of didiamide insecticides (flubendiamide, chlorantraniliprole, and cyantraniliprole) was introduced against P. xylostella 7,8 . But pest developed resistance against these insecticides within 18 months after introduction in the field 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…With the emergence of chlorantraniliproleresistant populations, several studies have shown changes in the locomotor activity of insects when exposed to surfaces treated with this insecticide-for example, the study by PLAtA-RUEDA et al (2019) on coffee borer beetle (Hypothenemus hampei), and studies by NANSEN et al (2016), CHANDI &SINGH (2017), andPASSOS et al (2019) on diamondback moth. Verifying changes in the locomotor activity of agricultural pests in response to exposure to the insecticide in each location is an issue, considering that this behavior can reduce the contact of the pest with the insecticide, thereby reducing the absorption of insecticide and causing a lower control efficacy (GUEDES et al, 2011).…”
Section: Introductionmentioning
confidence: 99%